Adsorption of D2O and CO on Co3O4(111): Water Stabilizes Coadsorbed CO - Fickenscher, Georg; Hohner, Chantal; Xu, Tao; Libuda, Jörg (Journal of Physical Chemistry C, 2021)
Water has a significant influence on the low-temperature CO oxidation on cobalt oxide. In this work, we studied the adsorption of CO and D2O on an atomically defined Co3O4(111) surface by infrared reflection absorption spectroscopy (IRAS). At 110 K, we find that CO binds initially to the Co2+sites at the surface (2174-2158 cm-1), while a second CO band with lower frequency (2132-2142 cm-1) appears at larger CO exposure. The origin of the second CO band has previously remained unclear. Here, we demonstrate that this band is associated with the coadsorption of water. Upon dosing D2O, CO on the pristine Co2+sites is successively displaced by CO on sites modified by coadsorbed water. Upon annealing, two new CO bands appear at 2105 and 2090 cm-1that are associated with the coadsorbed partially dissociated D2O wetting layer and coadsorbed partially dissociated D2O islands, respectively. Furthermore, the CO desorption temperature increases from 200 K in the absence of water to 250 K in the presence of water, i.e., the CO adsorption strength increases considerably in the presence of coadsorbed water. We propose that such coadsorption effects may play a major role for the catalytic activity of cobalt oxide surfaces.
CRIS-Team Scopus Importer:2021-12-24